Sosialisasi Kesehatan Reproduksi dan Persiapan Kehamilan dalam Perspektif Islam pada Calon Pengantin di KUA Kecamatan Simpang Mamplam Kabupaten Bireuen - Hilwa, Zaitun; agustina, Agustina; Fitria, Irma; Raudhati, Sri; Nova, Nova; Mawaddah, Mawaddah; Fitria, Ona (Universitas Baiturrahim, 2024)
Guidance for prospective brides (catin) is carried out to prepare Indonesian citizens who will marry and form a family, to make the family happy, to give birth to a valuable era and a good country. To achieve this goal, the Almuslim University Faculty of Health service team collaborated with the Ministry of Religion of Bireuen Regency to provide socialization or Health Education to prospective brides and grooms at the Religious Affairs Office (KUA), which is one of the KUA's tasks in pre-marital guidance activities for implementing marriage registration. The aim of carrying out this service activity is to provide education on the importance of pre-marital guidance regarding reproductive health and preparation for pregnancy viewed from an Islamic perspective for prospective brides and grooms in the KUA Simpang Mamplam District, Bireuen Regency. Issues regarding reproductive health and preparation for pregnancy from an Islamic perspective are still considered taboo to be discussed at this time, especially for the people of Aceh. To overcome this, it is necessary to carefully prepare information related to reproductive health with an Islamic perspective to prepare parents for building a household in the future. So, the target of this activity is the prospective groom and bride. Form health education activities, by planning, implementing and evaluating activities. The methods used are lecture, question and answer and discussion methods. The results obtained from this activity were that all Catins were very enthusiastic about participating in the outreach activities delivered by the team (100%), and from the results of the discussion/question and answer there were 3 people who did not understand the material presented (27%). From this activity, the service team recommends continuing to increase cooperation with the head of the local KUA to make it easier to implement/socialize premarital preparations towards a healthy and quality pregnancy.